Multiphase and multicomponent simulation of acid mine drainage in unsaturated mine waste: Modeling approach, benchmarks and application examples. (September 2020) - Muniruzzaman, Muhammad; Karlsson, Teemu; Ahmadi, Navid; Rolle, Massimo
Abstract: Acid mine drainage (AMD), caused by weathering of sulfide-rich mine wastes, is arguably the most critical environmental issue in the mining sector. Despite the fact that individual mechanisms responsible for the generation/propagation of AMD are fairly well-known, the prediction of overall dynamics in a mine waste system is challenging due to the nonlinearity and multilevel coupling associated with the key physico-chemical processes. This work presents a new three-phase multicomponent reactive transport model for AMD simulations, taking into account variably saturated water flow, multicomponent advective-dispersive transport both in aqueous and gaseous phase, and kinetic and equilibrium chemical reactions. The model is capable to capture the species-species coupling due to solute/surface charge or gas phase pressure by solving Nernst-Planck equation for the aqueous transport, and Maxwell-Stefan equation for the gaseous transport. Furthermore, the unsaturated flow and transport code is coupled with PHREEQC, utilizing the PhreeqcRM module, to simulate a wide range of geochemical reactions. The capabilities of the code are benchmarked against other software, previously published laboratory data, and pilot-scale drainage experiments in mica schist containing waste rocks performed in this study. The results are analyzed in terms of spatial and temporal profiles. The simulations reveal that the proposed model, called AMD-PHREEQC, is capable of accurately reproducing the experimental results, and thus it can be effectively used in environmental risk assessment, long-term drainage quality predictions, and data interpretations in mine waste. Highlights: Modeling approach for acid mine drainage (AMD) in unsaturated mine waste rocks. Multiphase and multicomponent transport with PhreeqcRM coupling for reactions. Benchmark and validation with other codes and experimental observations. Interpretation of long-term lysimeter AMD dataset in mica schist waste rocks.